Laminated cell and lithium ion secondary battery comprising same
By setting the base coat in the outermost electrode of the lithium-ion secondary battery laminated battery cell to regulate the resistivity and thickness, the problem of lithium-ion negative electrode or positive electrode is solved, and the safety and performance of the battery are improved .
Patent Information
- Application Number
- CN202411361926.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium evolution is likely to occur in the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the lithium-ion secondary battery laminated battery cell, resulting in battery performance and safety problems.
An outermost primer is provided between the current collector and the active material layer of the outermost electrode sheet so that the resistance of the remaining portion of the outermost electrode sheet except the active material layer is greater than that of the innermost electrode sheet except the active material layer. The resistance of the rest of the layer is reduced by regulating the resistivity of the outermost current collector, the resistivity of the outermost base coat, the thickness of the current collector and the thickness of the inner layer current collector Current density of current collector.
It effectively solves the problem of lithium excision of the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode, improves the safety performance and energy density of the battery, and avoids the occurrence of short circuits in the battery.
Smart Images

Figure CN119208756A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a laminated battery cell and a lithium-ion secondary battery containing the same. Background Art
[0002] With the development of lithium-ion batteries, consumers have higher and higher demands for charging speed and service life. Compared with wound structure batteries, laminated structure batteries have more uniform current density, faster acceptable reaction rate, and therefore faster charging speed. However, in the manufacturing process of laminated cells, the outermost current collector can often only be coated with active materials on one side. Single-sided coating will cause uneven stress distribution of the outermost current collector, which is prone to curling.
[0003] In order to avoid curling of the outermost electrode, the existing improvement measure is to make the thickness of the outermost current collector greater than the thickness of the inner current collector, but this brings new problems: due to the inconsistent thickness of the outermost current collector and the inner current collector, the ohmic internal resistance of the outermost current collector is smaller, and the current density is larger, which makes the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode prone to lithium deposition. Summary of the invention
[0004] The present application provides a laminated battery cell, which aims to solve to a certain extent the problem that the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the existing lithium-ion secondary battery laminated battery cell is prone to lithium deposition.
[0005] The present application also provides a lithium-ion secondary battery comprising the above-mentioned laminated battery cell.
[0006] In a first aspect, the present application provides a laminated battery cell, comprising a first pole piece, a diaphragm, and a second pole piece which are stacked, wherein the first pole piece and the second pole piece have opposite polarities, and the first pole piece comprises an inner pole piece and an outermost pole piece located outside the inner pole piece;
[0007] The inner electrode sheet comprises an inner current collector and an inner active material layer disposed on at least one side surface of the inner current collector;
[0008] The outermost electrode sheet includes an outermost current collector, an outermost primer layer and an outermost active material layer. The outermost primer layer is arranged on the surface of the outermost current collector facing the inner electrode sheet, and the outermost active material layer is arranged on the surface of the outermost primer layer away from the outermost current collector. The thickness of the outermost current collector is greater than the thickness of the inner current collector.
[0009] In an optional embodiment, the laminated battery core meets the following conditions:
[0010]
[0011] Among them, ρ 1 is the resistivity of the outermost current collector, in Ω·m; ρ 2 is the resistivity of the outermost bottom coating, in Ω·m; L is the length of the outermost electrode, in μm; H 1 is the thickness of the outermost current collector, in μm; H 2 H is the thickness of the outermost primer layer, in μm; 3 is the thickness of the inner current collector, in μm.
[0012] In an optional embodiment, the inner electrode sheet further includes an inner primer layer, which is disposed between the inner current collector and the inner active material layer, and the thickness of the inner primer layer is less than the thickness of the outermost primer layer.
[0013] In an optional embodiment, the laminated battery core meets the following conditions:
[0014]
[0015] Among them, ρ 1 is the resistivity of the outermost current collector, in Ω·m; ρ 2 is the resistivity of the outermost bottom coating, in Ω·m; L is the length of the outermost electrode, in μm; H 1 is the thickness of the outermost current collector, in μm; H 2 H is the thickness of the outermost primer layer, in μm; 3 is the thickness of the inner current collector, in μm; H 4 It is the thickness of the inner primer layer, in μm.
[0016] In an optional embodiment, the p 1 1.0×10 -8 Ω·m-2.82×10 -6 Ω·m.
[0017] In an optional embodiment, the p 2 0.01Ω·m-100Ω·m.
[0018] In an optional embodiment, the L is 3.0×10 4 μm-10.0×10 5 μm.
[0019] In an optional embodiment, the H 1 5μm-30μm.
[0020] In an optional embodiment, the H 2 1μm-8μm.
[0021] In an optional embodiment, the H 3 4μm-25μm.
[0022] In an optional embodiment, the H 4 0μm-4μm.
[0023] In an optional embodiment, the outermost primer layer and / or the inner primer layer comprises inorganic particles, a conductive agent and a binder, and the particle size Dv50 of the inorganic particles is 50 nm-2 μm.
[0024] In an optional embodiment, the mass ratio of the inorganic particles, the conductive agent and the binder is (10-60):(40-70):(2-20).
[0025] In an optional embodiment, the inorganic particles include at least one of aluminum oxide, silicon dioxide, calcified silicon, silicon carbide, boehmite, calcium carbonate, and olivine-like metal oxides.
[0026] In an optional embodiment, the conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanotubes, and graphene.
[0027] In an optional embodiment, the binder includes at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylonitrile, polystyrene-acrylate, polyacrylate and derivatives thereof.
[0028] In an optional embodiment, when the first electrode sheet is a positive electrode, the surface density σ of the outermost active material layer is 1 is smaller than the surface density σ of the inner active material layer 2 .
[0029] In an optional embodiment, when the first electrode sheet is a negative electrode, the surface density σ of the outermost active material layer is 1 Greater than the surface density σ of the inner active material layer 2 .
[0030] In an optional implementation, the σ 1 0.02kg / m 2 -0.3kg / m 2 .
[0031] In an optional implementation, the σ 2 0.02kg / m 2 -0.3kg / m 2 .
[0032] In an optional embodiment, the outermost current collector and / or the inner current collector is a composite current collector, and the composite current collector includes a support layer and a conductive layer arranged on both sides of the support layer, and the conductive layer is made of aluminum or copper.
[0033] In an optional embodiment, the composite current collector has a thickness of 10 μm-30 μm.
[0034] In an optional implementation, the thickness of the conductive layer is 0.5 μm-3 μm.
[0035] In a second aspect, the present application further provides a lithium-ion secondary battery, comprising the laminated battery cell described in the first aspect.
[0036] The technical solution of this application has the following advantages:
[0037] The laminated battery cell provided in the present application provides an outermost primer layer between the current collector and the active material layer of the outermost electrode sheet so that the resistance of the remaining part of the outermost electrode sheet except the active material layer is greater than the resistance of the remaining part of the inner electrode sheet except the active material layer, thereby solving the problem of lithium plating in the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode to a certain extent.
[0038] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 is a cross-sectional view in the height direction of a laminated battery core prepared in one embodiment of the present application;
[0041] Figure 2 yes Figure 1 Top view of the .
[0042] The reference numerals are described as follows:
[0043] 10. Outermost electrode sheet; 11. Outermost current collector; 12. Outermost undercoat layer; 13. Outermost positive electrode active material layer; 20. Diaphragm; 30. Inner negative electrode sheet; 31. Inner negative electrode active material layer; 32. Inner negative electrode current collector; 40. Inner positive electrode sheet; 41. Inner positive electrode active material layer; 42. Inner positive electrode current collector; 50 - pole ear. DETAILED DESCRIPTION
[0044] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0045] In the description of the present application, it should be noted that the terms "inside" and "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0047] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0048] The present application provides a laminated battery cell and a lithium-ion secondary battery, wherein the laminated battery cell can effectively solve the problem that the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the laminated battery cell of the lithium-ion secondary battery is prone to lithium deposition. The technical solution adopted by the present application is as follows.
[0049] In a first aspect, the present application provides a laminated battery cell, comprising a first pole piece, a diaphragm, and a second pole piece which are stacked, wherein the first pole piece and the second pole piece have opposite polarities, and the first pole piece comprises an inner pole piece and an outermost pole piece located outside the inner pole piece;
[0050] The inner electrode sheet comprises an inner current collector and an inner active material layer disposed on at least one side surface of the inner current collector;
[0051] The outermost electrode sheet includes an outermost current collector, an outermost primer layer and an outermost active material layer. The outermost primer layer is arranged on the surface of the outermost current collector facing the inner electrode sheet, and the outermost active material layer is arranged on the surface of the outermost primer layer away from the outermost current collector. The thickness of the outermost current collector is greater than the thickness of the inner current collector.
[0052] The laminated battery cell provided in the present application provides an outermost primer layer between the current collector and the active material layer of the outermost electrode sheet so that the resistance of the remaining part of the outermost electrode sheet except the active material layer is greater than the resistance of the remaining part of the inner electrode sheet except the active material layer, thereby solving the problem of lithium plating in the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode to a certain extent.
[0053] It should be noted that the laminated battery cell in the present application is stacked in the order of first electrode sheet-diaphragm-second electrode sheet-diaphragm-first electrode sheet-diaphragm...diaphragm-second electrode sheet-diaphragm-first electrode sheet, therefore, the first layer of the first electrode sheet stacked first and the last layer of the first electrode sheet stacked last are both the outermost electrode sheets, and the first electrode sheet between the first layer of the first electrode sheet stacked first and the last layer of the first electrode sheet stacked last is the inner electrode sheet. When the first electrode sheet is a positive electrode sheet, the negative electrode corresponding to the outermost positive electrode in the laminated battery cell is not prone to lithium deposition; or, when the first electrode sheet is a negative electrode sheet, the outermost negative electrode of the laminated battery cell is not prone to lithium deposition.
[0054] by Figure 1-2 As an example, the structure of a laminated battery cell in one embodiment of the present application is further described. Figure 1 As shown, in the height direction (z direction) of the laminated battery cell, the outermost electrode sheet 10, the separator 20, the inner negative electrode sheet 30, the separator 20, the inner positive electrode sheet 40... the separator 20, the inner negative electrode sheet 30, the separator 20 and the outermost electrode sheet 10 are stacked in sequence from top to bottom, wherein the outermost electrode sheet 10 includes a stacked outermost current collector 11, an outermost undercoat layer 12 and an outermost positive electrode active material layer 13; the inner negative electrode sheet 30 includes an inner negative electrode collector 32 and an inner negative electrode active material layer 31 arranged on two side surfaces in the thickness direction of the inner negative electrode collector 32; the inner positive electrode sheet includes an inner positive electrode collector 42 and an inner positive electrode active material layer 41 arranged on two side surfaces in the thickness direction of the inner positive electrode collector 42. Combined with Figure 2 The laminated cell further includes a pole ear 50, which further includes a positive pole ear and a negative pole ear. The positive pole ear is arranged at the end of the positive pole sheet in the width direction, and the negative pole ear is arranged at the end of the negative pole sheet in the width direction. Correspondingly, the direction perpendicular to the width direction is the length direction of the pole sheet, such as Figure 1 The x direction shown in .
[0055] This study found that by adjusting the resistivity ρ of the outermost current collector 1 (unit: Ω·m), the resistivity of the outermost primer layer ρ 2 (unit: Ω·m), the thickness of the outermost current collector H 1 (unit: μm), the thickness of the outermost primer layer H 2 (unit: μm), thickness of inner current collector H 3 (unit μm) and the length L of the outermost pole piece (unit μm, such as Figure 1 , Figure 2 The dimensions along the x direction shown in (shown in) satisfy the relationship: The current density of the outermost current collector can be reduced, and the problem of lithium plating at the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the lithium-ion secondary battery stack cell can be effectively solved.
[0056] Furthermore, an inner primer layer may be provided in the inner electrode sheet, wherein the inner primer layer is provided between the inner current collector and the inner active material layer, and the thickness of the inner primer layer is less than the thickness of the outermost primer layer.
[0057] The laminated battery core also meets the following conditions:
[0058]
[0059] Among them, ρ 1 is the resistivity of the outermost current collector, in Ω·m; ρ 2 is the resistivity of the outermost bottom coating, in Ω·m; L is the length of the outermost electrode, in μm; H 1 is the thickness of the outermost current collector, in μm; H 2 H is the thickness of the outermost primer layer, in μm; 3 is the thickness of the inner current collector, in μm; H 4 It is the thickness of the inner primer layer, in μm.
[0060] Based on the above solution, the present invention further provides an inner primer layer between the inner current collector and the inner active material layer, and the resistivity of the outermost current collector is 1 , the resistivity of the outermost primer layer ρ 2 , the thickness of the outermost current collector H 1 , the thickness of the outermost primer layer H 2 , the thickness of the inner current collector H 3 , the thickness of the inner primer layer H 4 And the length L of the outermost pole piece (such as Figure 1 , Figure 2 The dimensions along the x direction shown in This can not only reduce the current density of the outermost current collector, solve the problem of lithium plating in the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the lithium-ion secondary battery stack, but also reduce the occurrence of short circuit in the battery and ensure good safety performance.
[0061] It should be noted that in order to improve the puncture safety of lithium-ion secondary batteries, the relevant technology will introduce a primer structure in the pole piece, that is, first apply a primer on the positive current collector or the negative current collector, and then apply the positive active material or the negative active material on the primer; due to the presence of the primer, when the battery is abused by needle puncture, the binder will wrap the needle, reduce the contact between the negative electrode paste and the aluminum foil, reduce the risk of combustion, and thus improve the safety performance of lithium-ion secondary batteries. This application optimizes the existing primer structure, and controls the thickness and resistivity of the outermost primer and the thickness of the inner primer to satisfy the aforementioned relationship. On the one hand, it can ensure the safety of the battery, and on the other hand, it can also reduce the current density of the outermost current collector, solving the problem of lithium deposition in the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the lithium-ion secondary battery laminated cell.
[0062] In an optional embodiment, the p 1 1.0×10 -8 Ω·m-2.82×10 -6 Ω·m, as an example, ρ 1 It can be 1.0×10 -8 Ω·m、5.0×10 -8 Ω·m、1.0×10 -7 Ω·m、3.0×10 -7 Ω·m、5.0×10 -7 Ω·m、7.0×10 -7 Ω·m、9.0×10 -7 Ω·m、1.1×10 -6 Ω·m、2.82×10 -6 Ω·m, etc. or within the range of any two of the above values; or, the ρ 2 0.01Ω·m-100Ω·m, as an example, ρ 2 It can be 0.01Ω·m, 0.05Ω·m, 0.1Ω·m, 0.5Ω·m, 1.0Ω·m, 5.0Ω·m, 10Ω·m, 50Ω·m, 100Ω·m, etc. or within the range of any two of the above values. The present application has found that when the resistivity ρ of the outermost current collector is 1 Or the resistivity of the outermost primer layer ρ 2 When it is within the above range, the current density of the outermost electrode can be ensured to be reasonable, and lithium deposition in the outermost layer can be avoided; if the resistivity of the outermost current collector is 1Or the resistivity of the outermost primer layer ρ 2 If the value is too small, lithium deposition will easily occur in the outermost layer. On the contrary, if the resistivity of the outermost current collector is 1 Or the resistivity of the outermost primer layer ρ 2 If the value is too large, the overall cell polarization will be too large, affecting battery performance.
[0063] In an optional embodiment, the L is 3.0×10 4 μm-10.0×10 5 μm; as an example, L can be 3.0×10 4 μm, 7.0×10 4 μm, 1.0×10 5 μm, 3.0×10 5 μm, 6.0×10 5 μm, 8.0×10 5 μm, 10.0×10 5 μm, etc. or within the range of any two of the above values. This application study found that when the length of the outermost pole piece is 3.0×10 4 μm-6.0×10 5 μm range, the overall current density of the outermost electrode can be balanced; if the outermost electrode is too short, the current density of the outermost electrode collector will be larger, and lithium deposition will easily occur. On the contrary, if the outermost electrode is too long, the current density of the outermost electrode will be unevenly distributed, resulting in local lithium deposition problems.
[0064] In an optional embodiment, the H 1 5μm-30μm; as an example, H 1 It can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc. or within the range of any two of the above values. The present application has found that when the thickness H of the outermost current collector is 1 When it is in the range of 5μm-30μm, it can ensure that the outermost electrode is not easy to curl and lithium deposition does not occur on the outermost electrode; if the outermost current collector is too thick, it will lead to a large sacrifice in battery energy density and lithium deposition will easily occur on the outermost electrode; on the contrary, if the outermost current collector is too thin, the outermost layer will curl.
[0065] In an optional embodiment, the H 2 1μm-8μm, as an example, H 2 It can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc., or within the range of any two of the above values; or, the H 3 4μm-25μm, as an example, H 3It can be 4 μm, 10 μm, 15 μm, 20 μm, 25 μm, etc., or within the range of any two of the above values; or, the H 4 0μm-4μm, as an example, H 4 It can be 0 (i.e. no inner primer layer is provided), H 4 It can also be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc., or within the range of any two of the above values. The present application has found that when the thickness H of the outermost primer layer is 2 , the thickness of the inner current collector H 3 Or the thickness of the inner primer layer H 4 When within the above range, it can ensure that the battery energy density is not lost while the outermost electrode is not prone to lithium deposition; if the outermost bottom coating, the inner current collector or the inner bottom coating is too thick, it will cause excessive loss of battery energy density. On the contrary, if the outermost bottom coating or the inner current collector is too thin, lithium deposition will occur on the outermost electrode.
[0066] It is understood that the outermost primer layer and / or the inner primer layer of the present application include inorganic particles, a conductive agent and a binder, and the particle size Dv50 of the inorganic particles is 50nm-2μm, which can be measured by a laser particle size analyzer; as an example, the particle size Dv50 of the inorganic particles can be 50nm, 100nm, 250nm, 500nm, 750nm, 1μm, 1.5μm, 2μm, etc. or within the range of any two of the above values. The present application has found that when the particle size Dv50 of the inorganic particles is within the range of 50nm-2μm, a good conductive agent channel network can be established, thereby better adjusting the resistivity of the outermost primer layer and / or the inner primer layer, and also facilitating the preparation of the primer layer. If the particle size of the inorganic particles is too small, the conductive agent cannot effectively adhere to the surface of the inorganic particles to form an effective conductive network. On the contrary, if the particle size of the inorganic particles is too large, the conductive network formed will be unstable. In some embodiments, the inorganic particles include at least one of aluminum oxide, silicon dioxide, calcified silicon, silicon carbide, boehmite, calcium carbonate, and olivine-like metal oxides, wherein the olivine-like metal oxide may include lithium iron phosphate or lithium iron manganese phosphate; the conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanotubes, and graphene; the binder includes at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polystyrene-acrylate, polyacrylate, and derivatives thereof.
[0067] In an optional embodiment, the mass ratio of the inorganic particles, the conductive agent and the binder is (10-60): (40-70): (2-20), thereby forming a stable primer layer and providing a suitable resistivity. As an example, the mass ratio of the inorganic particles, the conductive agent and the binder in the outermost primer layer and / or the inner primer layer can be, for example, 10:70:20, 20:65:15, 30:60:10, 40:55:5, 50:45:5, 58:40:2, etc., or within the range of any two of the above values.
[0068] It should be noted that when the first electrode is the positive electrode, the surface density σ of the outermost active material layer is 1 Smaller than the surface density of the inner active material layer σ 2 , at this time, the positive electrode releases fewer lithium ions, which can alleviate the lithium precipitation of the corresponding negative electrode. When the first electrode is the negative electrode, the surface density of the outermost active material layer σ 1 Greater than the surface density of the inner active material layer σ 2 , then the negative electrode can receive more lithium ions and can slowly release lithium. In some embodiments of the present application, σ 1 0.02kg / m 2 -0.3kg / m 2 , σ 2 0.02kg / m 2 -0.3kg / m 2 , as an example, σ 1 and σ 2 Can independently take 0.02kg / m 2 , 0.06kg / m 2 , 0.1kg / m 2 , 0.15kg / m 2 , 0.2kg / m 2 , 0.25kg / m 2 , 0.3kg / m 2 The value is equal to or within the range formed by any two of the above values.
[0069] It is understandable that, compared with a current collector made of a single material, a composite current collector has advantages such as large internal resistance and high safety of needle puncture, so in an optional embodiment of the present application, the outermost current collector and / or the inner current collector is a composite current collector, and the composite current collector includes a support layer and a conductive layer arranged on both sides of the support layer, and the material of the conductive layer contains aluminum or copper. When the conductive layer is aluminum, the corresponding composite current collector is a positive electrode current collector, and when the conductive layer is copper, the corresponding composite current collector is a negative electrode current collector, that is, the positive electrode current collector and / or the negative electrode current collector in the present application can be a composite current collector. In some embodiments, the thickness of the composite current collector is 10 μm-30 μm. As an example, the thickness of the composite current collector can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc., or within the range of any two of the above values. The thickness of the conductive layer is 0.5 μm-3 μm, for example, it can be 0.5 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, etc., or within the range of any two of the above values.
[0070] In a second aspect, the present application further provides a lithium-ion secondary battery, comprising the laminated battery cell described in the first aspect.
[0071] It can be understood that the electrode sheet in the present application can be functionally divided into a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer, the positive electrode collector has two surfaces opposite to each other in its own thickness direction, the positive electrode active material layer is arranged on any one or both of the two opposite surfaces of the positive electrode collector, and the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The materials, composition and manufacturing method of the positive electrode sheet used in the lithium-ion secondary battery of the present application may include any technology disclosed in the prior art. As an example, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium-rich manganese-based materials. The negative electrode sheet includes a negative electrode collector and a negative electrode active material layer, the negative electrode collector has two surfaces opposite to each other in its own thickness direction, the negative electrode active material layer is arranged on any one or both of the two opposite surfaces of the negative electrode collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder. The materials, composition and manufacturing method of the negative electrode sheet used in the lithium-ion secondary battery of the present application may include any technology disclosed in the prior art. As an example, the negative electrode active material includes at least one of graphite and silicon-based materials, the silicon-based materials include silicon carbon and silicon oxygen, and the graphite includes artificial graphite and natural graphite.
[0072] Preferably, the negative electrode active material comprises a silicon-carbon material, and the content of the silicon-carbon material accounts for 4-30 wt % of the negative electrode active material.
[0073] The material and shape of the separator used in the lithium ion secondary battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.
[0074] The electrolyte used in the lithium ion secondary battery of the present application may include any technology disclosed in the prior art.
[0075] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit % represents the mass percentage content.
[0076] Example 1
[0077] (1) A primer slurry is prepared using alumina (Dv50 = 500 nm) as inorganic particles, conductive carbon black as a conductive agent, and PVDF as a binder: the above materials are mixed evenly in a ratio of 40% inorganic particles, 50% conductive agent, and 10% binder to obtain a primer slurry.
[0078] (2) Preparing positive electrode slurry with lithium cobalt oxide as positive electrode active material: According to the ratio of 96% positive electrode active material, 2.5% conductive carbon black, and 1.5% PVDF, the positive electrode slurry is prepared according to a certain batching process. The positive electrode slurry has a viscosity of 4000 mPa·s and a solid content of 72%.
[0079] (3) Preparing negative electrode slurry with graphite as negative electrode active material: preparing negative electrode slurry according to a certain batching process according to the ratio of negative electrode active material 96.8%, Super-P 1.2%, and CMC 2%. The viscosity of the negative electrode slurry is 4500mPa.s and the solid content is 45%.
[0080] (4) The primer slurry prepared in step (1) is coated on one surface of a 20 μm thick aluminum foil current collector and dried to form a 3 μm thick primer layer. The positive electrode slurry prepared in step (2) is then coated on the primer layer and dried to obtain an outermost positive electrode sheet with a length of 75 mm.
[0081] (5) The positive electrode slurry prepared in step (2) is coated on two opposite surfaces of a 10 μm thick aluminum foil current collector and dried to obtain an inner positive electrode sheet.
[0082] (6) The negative electrode slurry prepared in step (3) is coated on two opposite surfaces of a 6 μm thick copper foil current collector and dried to obtain an inner negative electrode sheet.
[0083] (7) The outermost positive electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then stacked to form a stacked battery cell, the structure of which is as follows: Figure 1 and Figure 2As shown; after passing the short-circuit test, it is packaged with aluminum-plastic film and baked in an oven to remove moisture. After the moisture standard required for liquid injection is reached, the electrolyte is injected. After aging for 24 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0084] The preparation methods and raw materials of Examples 2 to 10 are the same as those of Example 1, and the differences are shown in Table 1.
[0085] Embodiment 11
[0086] (1) Prepare a primer slurry with alumina (Dv50 = 50 nm) as inorganic particles, Super-P as a conductive agent, and polyacrylonitrile as a binder: mix the above materials evenly according to the ratio of 10% inorganic particles, 70% conductive agent, and 20% binder to obtain a primer slurry.
[0087] (2) Preparing positive electrode slurry with lithium manganese iron phosphate as positive electrode active material: According to the ratio of 95% positive electrode active material, 3% acetylene black, and 2% PVDF, the positive electrode slurry is prepared according to a certain batching process, the slurry viscosity is 5000mPa·s, and the solid content is 70%.
[0088] (3) Preparing negative electrode slurry with graphite as negative electrode active material: According to the ratio of 96% negative electrode active material, 2% acetylene black, and 2% PVDF, the negative electrode slurry is prepared according to a certain batching process, the slurry viscosity is 3000mPa.s, and the solid content is 45%.
[0089] (4) The primer slurry prepared in step (1) is coated on one surface of a 25 μm thick composite aluminum foil current collector (2.5 μmAl / 20 μmPET / 2.5 μmAl), and dried to form a 4 μm thick primer layer. The positive electrode slurry prepared in step (2) is then coated on the primer layer and dried to obtain an outermost positive electrode sheet with a length of 100 mm.
[0090] (5) The primer slurry prepared in step (1) is coated on two opposite surfaces of a 20 μm thick composite aluminum foil current collector (2 μmAl / 16 μmPET / 2 μmAl), and dried to form two 1 μm thick primer layers. The positive electrode slurry prepared in step (2) is then coated on the two primer layers, and dried to obtain an inner positive electrode sheet.
[0091] (6) The negative electrode slurry prepared in step (3) is coated on both surfaces of a 6 μm thick copper foil current collector pair and dried to obtain an inner negative electrode sheet.
[0092] (7) The outermost positive electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then assembled into a laminated battery cell by lamination. After passing the short-circuit test, they are packaged with aluminum plastic film and baked in an oven to remove moisture. After the moisture standard required for liquid injection is reached, the electrolyte is injected. After aging for 48 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0093] Example 12
[0094] (1) Prepare a primer slurry with silica (Dv50 = 300 nm) as inorganic particles, graphene as a conductive agent, and PVDF as a binder: mix the above materials evenly according to the ratio of 25% inorganic particles, 60% conductive agent, and 15% binder to obtain a primer slurry.
[0095] (2) Using lithium iron phosphate as the positive electrode active material to prepare positive electrode slurry: According to the ratio of 97.5% of positive electrode active material, 2% of conductive carbon black, and 1.5% of PVDF, the positive electrode slurry is prepared according to a certain batching process. The slurry viscosity is 4000 mPa·s and the solid content is 75%.
[0096] (3) A negative electrode slurry was prepared using silicon carbon (containing 5% silicon) as the negative electrode active material: the negative electrode slurry was prepared according to a certain batching process according to a ratio of 97% negative electrode active material, 1.5% conductive carbon black, and 1.5% PVDF. The slurry had a viscosity of 2000 mPa.s and a solid content of 40%.
[0097] (4) The primer slurry prepared in step (1) is coated on one surface of a 20 μm thick composite aluminum foil current collector (3 μmAl / 14 μmPET / 3 μmAl), and dried to form a 5 μm thick primer layer. The positive electrode slurry prepared in step (2) is then coated on the primer layer and dried to obtain an outermost positive electrode sheet with a length of 50 mm.
[0098] (5) The primer slurry prepared in step (1) is coated on two opposite surfaces of a 10 μm thick composite aluminum foil current collector (1 μmAl / 8 μmPET / 1 μmAl), and dried to form two 2 μm thick primer layers. The positive electrode slurry prepared in step (2) is then coated on the two primer layers, and dried to obtain an inner positive electrode sheet.
[0099] (6) The primer slurry prepared in step (3) is coated on two opposite surfaces of a 6 μm thick copper foil current collector and dried to obtain an inner negative electrode sheet.
[0100] (7) The outermost positive electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then assembled into a laminated battery cell by lamination. After passing the short-circuit test, they are packaged with aluminum plastic film and baked in an oven to remove moisture. After the moisture standard required for liquid injection is reached, the electrolyte is injected. After aging for 36 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0101] Embodiment 13
[0102] (1) Prepare a primer slurry using lithium iron phosphate (Dv50 = 500 nm) as inorganic particles, acetylene black as a conductive agent, and SBR as a binder: mix the above materials evenly according to the ratio of 35% inorganic particles, 60% conductive agent, and 5% binder to obtain a primer slurry.
[0103] (2) Using lithium cobalt oxide as the positive electrode active material to prepare positive electrode slurry: According to the ratio of 98.2% of positive electrode active material, 1% of conductive carbon black, and 0.8% of SBR, the positive electrode slurry is prepared according to a certain batching process, the slurry viscosity is 2000 mPa·s, and the solid content is 80%.
[0104] (3) Using silicon carbon (containing 6% silicon) as the negative electrode active material to prepare the negative electrode slurry: According to the ratio of 97.5% of negative electrode active material, 1% of conductive carbon black, and 1.5% of PVDF, the negative electrode slurry is prepared according to a certain batching process. The slurry viscosity is 5000mPa.s and the solid content is 50%.
[0105] (4) The primer slurry prepared in step (1) is coated on one surface of a 20 μm thick aluminum foil current collector and dried to form a 4 μm thick primer layer. The positive electrode slurry prepared in step (2) is then coated on the primer layer and dried to obtain an outermost positive electrode sheet with a length of 50 mm.
[0106] (5) The primer slurry prepared in step (1) is coated on two opposite surfaces of a 10 μm thick aluminum foil current collector and dried to form two 1 μm thick primer layers. The positive electrode slurry prepared in step (2) is then coated on the two primer layers and dried to obtain an inner positive electrode sheet.
[0107] (6) The negative electrode slurry prepared in step (3) is coated on two opposite surfaces of a 6 μm thick copper foil current collector and dried to obtain an inner negative electrode sheet.
[0108] (7) The outermost positive electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then assembled into a laminated battery cell by lamination. After passing the short-circuit test, they are packaged with aluminum plastic film and baked in an oven to remove moisture. After the moisture standard required for liquid injection is reached, the electrolyte is injected. After aging for 30 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0109] Embodiment 14
[0110] (1) Prepare a primer slurry using boehmite (Dv50 = 1 μm) as inorganic particles, acetylene black as a conductive agent, and polyacrylate as a binder: mix the above materials evenly according to the ratio of 40% inorganic particles, 50% conductive agent, and 10% binder to obtain a primer slurry.
[0111] (2) Using lithium iron phosphate as the positive electrode active material to prepare positive electrode slurry: According to the ratio of 97% positive electrode active material, 1% conductive carbon black, and 2% PVDF, the positive electrode slurry is prepared according to a certain batching process, the slurry viscosity is 7000 mPa·s, and the solid content is 75%.
[0112] (3) Preparing negative electrode slurry with graphite as negative electrode active material: According to the ratio of 96% negative electrode active material, 2.5% conductive carbon black, and 1.5% PVDF, the negative electrode slurry is prepared according to a certain batching process. The slurry viscosity is 4000mPa.s and the solid content is 50%.
[0113] (4) The primer slurry prepared in step (1) is coated on one surface of a 16 μm thick copper foil current collector and dried to form a 3 μm thick primer layer. The negative electrode slurry prepared in step (3) is then coated on the primer layer and dried to obtain an outermost negative electrode sheet with a length of 120 mm.
[0114] (5) The negative electrode slurry prepared in step (3) is coated on two opposite surfaces of a 6 μm thick copper foil current collector and dried to obtain an inner negative electrode sheet.
[0115] (6) The positive electrode slurry prepared in step (2) is coated on two opposite surfaces of a 10 μm thick aluminum foil current collector and dried to obtain an inner positive electrode sheet.
[0116] (7) The outermost negative electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then assembled into a laminated battery cell by lamination; after passing the short-circuit test, they are packaged with aluminum plastic film, baked in an oven to remove moisture, and then the electrolyte is injected until the moisture standard required for liquid injection is reached. After aging for 36 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0117] Embodiment 15
[0118] (1) Prepare a primer slurry with calcium carbonate (Dv50 = 200 nm) as inorganic particles, super p as a conductive agent, and PVDF as a binder: mix the above materials evenly according to the ratio of 40% inorganic particles, 40% conductive agent, and 20% binder to obtain a primer slurry.
[0119] (2) Using nickel cobalt manganese oxide NCM811 as the positive electrode active material to prepare positive electrode slurry: According to the ratio of 98% positive electrode active material, 1% conductive carbon black, and 1% PVDF, the positive electrode slurry is prepared according to a certain batching process, the slurry viscosity is 4500mPa·s, and the solid content is 80%.
[0120] (3) Preparing negative electrode slurry with graphite as negative electrode active material: According to the ratio of 96% negative electrode active material, 1.5% conductive carbon black, and 2.5% PVDF, the negative electrode slurry is prepared according to a certain batching process. The slurry viscosity is 2500mPa.s and the solid content is 45%.
[0121] (4) The primer slurry prepared in step (1) is coated on one surface of a 28 μm thick composite copper foil current collector (3 μm Cu / 22 μm PET / 3 μm Cu), and dried to form a 5 μm thick primer layer. The negative electrode slurry prepared in step (3) is then coated on the primer layer and dried to obtain an outermost negative electrode sheet with a length of 300 mm.
[0122] (5) The positive electrode slurry prepared in step (2) is coated on two opposite surfaces of a 25 μm thick composite aluminum foil current collector (1 μmAl / 23 μmPET / 1 μmAl), and dried to obtain an inner positive electrode sheet.
[0123] (6) The negative electrode slurry prepared in step (3) is coated on two opposite surfaces of a 25 μm thick composite copper foil current collector (1.5 μm Cu / 22 μm PET / 1.5 μm Cu), and dried to obtain an inner negative electrode sheet.
[0124] (7) The outermost negative electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then assembled into a laminated battery cell by lamination. After passing the short-circuit test, they are packaged with aluminum plastic film and baked in an oven to remove moisture. After the moisture standard required for liquid injection is reached, the electrolyte is injected. After aging for 36 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0125] Example 16
[0126] (1) Prepare a primer slurry with calcified silicon (Dv50 = 600 nm) as inorganic particles, super p as a conductive agent, and polyacrylate as a binder: mix the above materials evenly according to the ratio of 55% inorganic particles, 40% conductive agent, and 5% binder to obtain a primer slurry.
[0127] (2) Using nickel cobalt manganese oxide NCM622 as the positive electrode active material to prepare positive electrode slurry: According to the ratio of 96.5% of positive electrode active material, 2% of conductive carbon black, and 1.5% of PVDF, the positive electrode slurry was prepared according to a certain batching process. The slurry viscosity was 6500 mPa·s and the solid content was 72%.
[0128] (3) Preparing negative electrode slurry with graphite as negative electrode active material: According to the ratio of 97.5% of negative electrode active material, 1.5% of conductive carbon black and 1% of PVDF, the negative electrode slurry is prepared according to a certain batching process. The slurry viscosity is 4500mPa.s and the solid content is 47%.
[0129] (4) The primer slurry prepared in step (1) is coated on one surface of a 30 μm thick copper foil current collector and dried to form an 8 μm thick primer layer. The negative electrode slurry prepared in step (3) is then coated on the primer layer and dried to obtain an outermost negative electrode sheet with a length of 600 mm.
[0130] (5) The primer slurry prepared in step (1) is coated on two opposite surfaces of a 26 μm thick copper foil current collector and dried to form two 1 μm thick primer layers. The negative electrode slurry prepared in step (3) is then coated on the two primer layers and dried to obtain an inner negative electrode sheet.
[0131] (6) The primer slurry prepared in step (1) is coated on two opposite surfaces of a 26 μm thick aluminum foil current collector and dried to form two 1 μm thick primer layers. The positive electrode slurry prepared in step (2) is then coated on the two primer layers and dried to obtain an inner positive electrode sheet.
[0132] (7) The outermost negative electrode sheet, inner positive electrode sheet and inner negative electrode sheet obtained above are rolled, die-cut and slit, and then assembled into a laminated battery cell by lamination. After passing the short-circuit test, they are packaged with aluminum plastic film and baked in an oven to remove moisture. After the moisture standard required for liquid injection is reached, the electrolyte is injected. After aging for 36 hours, the first charge is completed by a hot pressing process to obtain an activated lithium-ion battery.
[0133] The preparation method of Example 17 is the same as that of Example 1, with the only difference being that the particle size Dv50 of the inorganic particles in the base coating layer is 2 μm.
[0134] The preparation methods of Comparative Examples 1-4 refer to Example 1.
[0135] The preparation method of Comparative Example 5 is basically the same as that of Example 1, with the only difference being that in step (4), the positive electrode slurry is first coated on one surface of the aluminum foil current collector and dried to form an active material layer, and then the primer slurry is coated on the active material layer and dried to obtain the outermost positive electrode sheet.
[0136] The preparation methods of Comparative Examples 6-9 refer to Example 14.
[0137] The preparation method of Comparative Example 10 is basically the same as that of Example 14, with the only difference being that in step (4), the negative electrode slurry is first coated on one surface of the copper foil current collector and dried to form an active material layer, and then the primer slurry is coated on the active material layer and dried to obtain the outermost negative electrode sheet.
[0138] Test Case
[0139] 1. Resistivity test
[0140] The four-probe resistance meter is used for testing. First, ensure that the sample surface is clean and flat. Then, four equally spaced probes are placed vertically on the sample surface. A constant small current is applied through the outer probes. At the same time, the voltage between the inner probes is measured. The resistance value is calculated according to Ohm's law. Finally, the resistivity is calculated according to the resistivity formula based on the geometric dimensions of the sample. This process needs to be carried out in a stable state with controlled environmental conditions to ensure the accuracy and repeatability of the measurement.
[0141] 2. Surface density test
[0142] The active material (positive / negative electrode material) of the battery is evenly coated on the current collector, and then the mass difference of the current collector before and after coating is weighed, combined with the area of the coating area, to calculate the mass of the active material per unit area, that is, the surface density. This process requires precise weighing tools (such as electronic balances) and accurate area measurement to ensure the accuracy of the results.
[0143] 3. Cycle test
[0144] After 800 cycles of charging at a 3C rate and discharging at a 1C rate, the battery capacity and initial capacity were tested and the capacity retention rate was calculated. The battery was then dissected to observe whether the outermost current collector was curled and whether lithium deposition occurred on the outermost current collector or the corresponding negative electrode sheet.
[0145] In Examples 1-14 and Comparative Examples 1-8 of the present application, the material, thickness H1, and resistivity ρ of the outermost current collector are 1 , the thickness of the outermost primer layer H 2 , resistivity ρ 2 , the thickness of the inner current collector H 3 , the thickness of the inner primer layer H 4 , the length of the outermost electrode L, the surface density of the outermost active material layer σ 1 , the surface density of the inner active material layer σ 2 The values of the parameters are shown in Table 1, where “ / ” represents that the item does not exist; the battery cycle test results are shown in Table 2.
[0146] Table 1 Structure and physical parameters of laminated cells in various embodiments and comparative examples
[0147]
[0148]
[0149] Table 2 Cyclic performance of lithium-ion batteries in various embodiments and comparative examples
[0150]
[0151]
[0152] Combining Table 1 and Table 2, it can be seen that after the cycle test, the outermost current collector of the lithium ion batteries of Examples 1-10, Examples 13-14 and Examples 16-17 did not curl, and the outermost current collector or the corresponding negative electrode sheet did not undergo lithium deposition, which shows that the laminated battery of the present application can adjust the resistivity ρ of the outermost current collector. 1 , the resistivity of the outermost primer layer ρ 2 , the thickness of the outermost current collector H 1 , the thickness of the outermost primer layer H 2 , the thickness of the inner current collector H 3 and the length L of the outermost pole piece satisfy This can effectively solve the problem of lithium plating at the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the lithium-ion battery stack.
[0153] After the lithium-ion batteries of Examples 11-12 and Example 15 were cycled, the outermost current collector did not curl, and the outermost current collector or the corresponding negative electrode sheet did not undergo lithium deposition, which indicates that the laminated battery of the present application can be obtained by adjusting the resistivity ρ of the outermost current collector. 1 , the resistivity of the outermost primer layer ρ 2 , the thickness of the outermost current collector H 1 , the thickness of the outermost primer layer H 2 , the thickness of the inner current collector H 3 , the thickness of the inner primer layer H 4 and the length L of the outermost pole piece satisfy This can effectively solve the problem of lithium plating at the outermost negative electrode or the negative electrode corresponding to the outermost positive electrode in the lithium-ion battery stack.
[0154] Compared with Example 1, although the outermost primer layer is provided in Comparative Example 1, the thickness of the outermost current collector is consistent with the thickness of the inner current collector, resulting in the curling of the outermost current collector after the battery cycle test, affecting the battery performance, life and safety; although the outermost current collector in the battery of Comparative Example 2 is not curled, the problem of lithium precipitation of the outermost current collector cannot be solved because the outermost primer layer is not provided; Comparative Example 3 does not have an outermost primer layer, and the thickness of the outermost current collector is consistent with the thickness of the inner current collector, resulting in the curling of the outermost current collector after the battery cycle test, and lithium precipitation also occurs in the negative electrode sheet corresponding to the outermost current collector; the thickness of the outermost current collector of Comparative Example 4 is greater than the thickness of the inner current collector, but does not meet the Therefore, after the battery cycle test, the outermost current collector did not curl, but lithium deposition occurred in the negative electrode sheet corresponding to the outermost current collector; in Comparative Example 5, the positions of the outermost undercoat layer and the outermost active material layer were interchanged. At this time, the outermost undercoat layer could not reduce the current density of the outermost current collector, and therefore could not solve the lithium deposition problem.
[0155] Comparative Examples 6 to 10 are the same as Comparative Examples 1 to 5, respectively, and thus will not be described in detail.
[0156] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A laminated battery cell, comprising a first pole piece, a diaphragm and a second pole piece which are stacked, wherein the first pole piece and the second pole piece have opposite polarities, and the first pole piece comprises an inner pole piece and an outermost pole piece located outside the inner pole piece; The inner electrode sheet comprises an inner current collector and an inner active material layer disposed on at least one side surface of the inner current collector; It is characterized in that The outermost electrode sheet includes an outermost current collector, an outermost primer layer and an outermost active material layer. The outermost primer layer is arranged on the surface of the outermost current collector facing the inner electrode sheet, and the outermost active material layer is arranged on the surface of the outermost primer layer away from the outermost current collector. The thickness of the outermost current collector is greater than the thickness of the inner current collector.
2. The laminated battery cell according to claim 1, characterized in that: The following conditions must be met: Among them, ρ1 is the resistivity of the outermost current collector, unit Ω·m; ρ2 is the resistivity of the outermost bottom coating, unit Ω·m; L is the length of the outermost pole piece, unit μm; H1 is the thickness of the outermost current collector, unit μm; H2 is the thickness of the outermost bottom coating, unit μm; H3 is the thickness of the inner current collector, unit μm.
3. The laminated battery cell according to any one of claims 1 to 2, characterized in that: The inner electrode sheet further comprises an inner primer layer, the inner primer layer is disposed between the inner current collector and the inner active material layer, and the thickness of the inner primer layer is less than the thickness of the outermost primer layer; Preferably, it also satisfies: Among them, ρ1 is the resistivity of the outermost current collector, unit Ω·m; ρ2 is the resistivity of the outermost bottom coating, unit Ω·m; L is the length of the outermost pole piece, unit μm; H1 is the thickness of the outermost current collector, unit μm; H2 is the thickness of the outermost bottom coating, unit μm; H3 is the thickness of the inner current collector, unit μm; H4 is the thickness of the inner bottom coating, unit μm.
4. The laminated battery cell according to claim 2 or 3, characterized in that: The ρ1 is 1.0×10 -8 Ω·m - 2.82×10 -6 Ω·m; And / or, ρ2 is 0.01Ω·m-100Ω·m; and / or, said L is 3.0×10 4 μm-10.0×10 5 μm; And / or, H1 is 5 μm-30 μm; And / or, H2 is 1 μm-8 μm; And / or, H3 is 4 μm-25 μm; And / or, H4 is 0 μm-4 μm.
5. The laminated battery cell according to any one of claims 1 to 4, characterized in that: The outermost primer layer and / or the inner primer layer comprises inorganic particles, a conductive agent and a binder, and the particle size Dv50 of the inorganic particles is 50 nm-2 μm.
6. The laminated battery cell according to claim 5, characterized in that: The mass ratio of the inorganic particles, the conductive agent and the binder is (10-60):(40-70):(2-20); and / or, the inorganic particles include at least one of aluminum oxide, silicon dioxide, calcified silicon, silicon carbide, boehmite, calcium carbonate, and olivine-like metal oxides; And / or, the conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanotubes, and graphene; And / or, the binder includes at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylonitrile, polystyrene-acrylate, polyacrylate and derivatives thereof.
7. The laminated battery cell according to any one of claims 1 to 4, characterized in that: When the first pole piece is a positive electrode, the surface density σ1 of the outermost active material layer is less than the surface density σ2 of the inner active material layer; Alternatively, when the first electrode sheet is a negative electrode, the surface density σ1 of the outermost active material layer is greater than the surface density σ2 of the inner active material layer; Preferably, the σ1 is 0.02 kg / m 2 -0.3kg / m 2 ; Preferably, the σ2 is 0.02 kg / m 2 -0.3kg / m 2 .
8. The laminated battery cell according to any one of claims 1 to 4, characterized in that: The outermost current collector and / or the inner current collector is a composite current collector, The composite current collector includes a support layer and a conductive layer arranged on both sides of the support layer, and the conductive layer is made of aluminum or copper.
9. The laminated battery cell according to claim 8, characterized in that: The composite current collector has a thickness of 10 μm-30 μm; and / or the conductive layer has a thickness of 0.5 μm-3 μm.
10. A lithium-ion secondary battery comprising the laminated battery cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Positive electrode current collector laminate for lithium secondary battery
CN102648546A
Cell and secondary battery comprising same
CN108878770A
Flexible lithium ion battery and preparation method thereof
CN111682267A
Laminated battery cell and lithium ion battery
CN112271341A
Lithium battery and preparation method thereof
CN117438664A
